Pengendalian Persedian Barang Dagang Pada UMKM Ayam Geprek Dalam Meningkatkan Daya Saing Usaha - Ferna Kaswanti; Nadya Violeta Amanda; Nisaul Hasanah; Lusiana . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in supporting the national economy, yet they still face various operational challenges, particularly in inventory control. Unplanned inventory management and the absence of systematic record-keeping can potentially lead to excess stock, raw material shortages, and operational cost inefficiencies, all of which can impact service quality and business competitiveness. This study aims to analyze the inventory control system of merchandise at the Nelo Ayam Geprek UMKM, identify problems that occur in stock management, and evaluate its contribution to increasing business competitiveness.This research employed a qualitative approach with a case study approach. The population comprised all parties involved in inventory management, with a sample of four informants consisting of the owner and three employees. Data collection techniques included observation, in-depth interviews, and documentation. Data sources included primary and secondary data. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with validity testing using source and technique triangulation.The results of the study indicate that the inventory control system is not yet structured, there is no consistent stock recording, and the calculation of the economic order quantity has not been implemented. Simulation of the Economic Order method. Implementing a planned inventory control system and optimal ordering calculations can improve operational efficiency, maintain production stability, and strengthen the competitiveness of MSMEs in a sustainable manner.